Diagnóstico e proposição de melhorias no sistema de tratamento de efluentes de um laticínio - Navarro, Karina Cerqueira (2016)
This study has as main objective to carry out the diagnosis and a characterization of the effluent treatment system of a cheese industry, located in the Southwest of the State of Paraná. It also seeks to evaluate its efficiency and to prepare a prognosis, mainly aiming at the removal of pollutants. From the detailed diagnosis, done by the collection of qualitative data, such as the arrangement of the units that make up the treatment system and on-site observations, as well as quantitative data of the laboratory analyzes, dimensions of the treatment units, hydraulic retention time etc., it was observed that in the Preliminary Treatment the bars of the railing are too spaced, the hydraulic retention times in the oil and grease retention tanks 1 and 2 were higher than recommended (TDH1 = 1 hora e 36 minutes and TDH2 = 2 horas e 15 minutes) application rates were low (1,120 m³.m-2.h-1 and 0,6 m³.m-2.h-1 respectively). In the Secondary Treatment, the TDH of the anaerobic pond was 58 days, much higher than that recommended by the literature, with a minimum organic matter removal of 53.60% and a maximum of 87.82%, while the TDH of the facultative pond was 90 days, with a minimum efficiency removal of 19.02% and maximum of 72.36%. Thus, improvements were proposed in the system to optimize the treatment and to meet the quality standards required by the environmental agency.